Differences In Knee Valgus Degrees In Cutting And Drop Landing On The Dominant And Non-Leg Dominant In High School Basketball Players - Bila, Dhea Salsa; Irawan, Dimas Sondang; Rahim, Anita Faradilla (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Background: Basic techniques, physical endurance, and teamwork in basketball are components needed to improve individual quality to be able to play with good performance. Basic techniques and movements often occur quickly and suddenly, including cutting and drop landing. Both of these movements are prone to knee injury. The majority of lower extremity injuries in basketball players are anterior cruciate ligament (ACL) strains. Observation of the knee valgus angle is required to assess the risk of knee injury. One of the risks has the potential to cause a knee injury is the dominant and non-dominant knee. This is because the leg have an important role in controlling posture and stability. Purpose: this study was to determine the differences in the risk factors for the dominant and non-dominant leg in cutting and drop landing. Methods: The research was analytic observational, a cross-sectional study design. The population in this study were high school basketball players in Malang City with a total sample of 22 people the inclusion and exclusion criteria (n=22). Data collection was carried outthe Waterloo Footedness Questionnaire-Revised (WFQ-R) and Frontal Plane Projection Angle (FPPA) as measuring tools using the kinovea software. Results: Based on the analysis Wilcoxon test forcutting and drop landing movements, a value of 0.036 (p <0.05) was obtained for the non-dominant leg, which means that there is a significant difference between the two movements. Conclusion: It canbe concluded that there are differences movements of cutting and drop landing on the non-dominant leg compared to the dominant leg.